Selfish Node Detection in Wireless Networks - Nivetha, D; Karthika, D (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad-hoc networks (MANETs) relies on upon network participation plans to work legitimately. It expects that mobile node deliberate participate so as to work appropriately. By and by, if nodes have a selfish conduct and are unwilling to participate, the general network execution could be genuinely degraded. The proposed framework builds up a homomorphic straight Authenticator based upon examining design that enables the identifier to confirm the honesty of the bundle misfortune data detailed with nodes. In this manner, by recognizing the correlations between lost bundles, one can choose whether the parcel misfortune is absolutely because of normal connection blunders, or is a consolidated impact of connection mistake and selfish node. In our project we have proposed an efficient method for detecting a selfish node which takes into account the various factors like the battery capacity of a node, power consumption in transmitting packets and to overcome the presence of selfish nodes. In this framework consists of degree of intrinsic selfishness (DeIS) and the degree of extrinsic selfishness (DeES). Under the distributed node-selfishness management, a path selection criterion is designed to select the most reliable and shortest path in terms of RNs’. The theoretical analysis and results show that the proposed model has better probability and efficiency.